Association Development and Professional Transformation model for nurse leaders. (25th September 2018) - Spencer, Sharon; Bianchi, Ann; Buckner, Ellen
Abstract : Aims: This pilot study evaluated an Association Development and Professional Transformation (ADAPT) model for nursing leadership development and assessed satisfaction with the ADAPT workshop. Background: Nurses often lack self‐confidence and self‐efficacy in leadership roles. There is a need for nurses to take leadership opportunities that serve to advance the nursing profession. Methods: A quasi‐experimental pre‐test post‐test design was used. The sampling method selected professional nursing association (PNA) members. Novice participants completed a pre‐assessment and post‐assessment Leadership Practice Inventory‐Self (LPI‐S) survey and attended the ADAPT workshop. Experienced nurse leaders participated as mentors. Both groups completed a satisfaction survey after the workshop. Results: Awareness of nursing leadership behaviours increased. Total mean scores for each subscale on the LPI‐S increased but this was not statistically significant. All participants reported satisfaction with the ADAPT workshop. Conclusions: This study offers evidence that the ADAPT model influences leadership behaviours. The ADAPT workshop provided a method to gain a leadership perspective and to encourage nurses to fulfil a leadership role within professional nursing associations. Implications for Nursing Management: Organisations and professional nursing associations that support the leadership potential of nurses must invest in providing leadership development opportunities.